Numberical simulation of flow around a circular cylinder with two splitter plates - Phan , Đức Huynh; Nguyen, Trần Bá Đình (Journal of Technical Education Science, 2019)
In this paper, the immersed boundary method is used to simulate of flow around a circular cylinder with two splitter plates. This simulation is performed within the unstable flow regime with the Renolds number of 100. Two splitter plates are arranged in parallel and symmetric through the horizontal centerline of the circular cylinder. Attachment angle of splitter plates can change within a range θf = 10° - 80°. This system creates the main vortex and sub-vortex which are aligned symmetrically through the centerline between the two plates. These two types of vortex interact with each other that leads to changes in drag and lift coefficient of the fluid acting on the structure. This interaction can suppress vibrations is formed by the interaction between fluid and structure. In addition, the influence of θf to the drag and lift coefficient of the fluid acting on the structure is also investigated. The result shows that these coefficients reach the minimum value when θf within range 30° ≤ θf ≤ 40°.